Self-Guided Smartphone Excursions in University Teaching—Experiences From Exploring “Water in the City” - Schwarzenbach, Franziska M.; Seibert, Jan; van Meerveld, H. J. (Ilja) (Frontiers in Environmental Science, 2022)
A few weeks after the start of the semester in spring 2020, our university switched to online-only teaching due to the pandemic. Like many other university teachers, we were faced with an unprecedented situation and had to cancel on-site teaching and excursions. However, we were in the fortunate position that we had already started to develop a smartphone-based self-guided excursion on the topic of ‘Water in the City’. We accelerated this development and used it to replace the traditional group excursion in our first-year Bachelor level introductory course in Hydrology. The excursion of this course is visited by around 150 students each year. Because the student feedback was overall very positive, we used the self-guided excursion again in 2021 and plan to continue to use it in the coming years. In this article, we describe the excursion, discuss the experiences of the students and ourselves, and present recommendations and ideas that could be useful for similar excursions at other universities.